Sodium alginate microspheres as well as preparation method and application thereof

By using cellulose and etching liquid in the preparation process of sodium alginate microspheres, a rich pore structure is formed, which solves the problem of low drug loading rate of sodium alginate microspheres, and achieves a higher drug loading rate and a more flexible sustained release effect.

CN119606924APending Publication Date: 2025-03-14GUANGZHOU KONCEN BIOSCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411921756.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The small pores and small specific surface area of ​​sodium alginate microspheres lead to a lower drug loading rate.

Method used

By adding a suspension containing cellulose and sodium alginate to the oil phase for emulsification, a water-in-oil emulsion is formed and cross-linked with a cross-linking agent to obtain the original microspheres. Then, the original microspheres are treated with an etching solution to promote cellulose degradation, form a rich pore structure, and improve the specific surface area and drug loading rate.

Benefits of technology

It increases the drug loading rate of sodium alginate microspheres, increases the specific surface area, reduces the density, adapts to different drug loading needs, and achieves differentiated sustained release and synchronous loading of drugs of different molecular weights.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119606924A_ABST
    Figure CN119606924A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of drug carriers, and discloses a sodium alginate microsphere and a preparation method and application thereof.The preparation method comprises the steps that a suspension containing cellulose and sodium alginate is added into an oil phase to be emulsified, a water-in-oil emulsion is formed, then a cross-linking agent is stirred and mixed to be subjected to a cross-linking reaction with the water-in-oil emulsion, original microspheres are obtained, and the sodium alginate microsphere is prepared. Finally, the original microspheres are treated with etching liquid, and the sodium alginate microspheres are obtained. According to the water-in-oil emulsion, cellulose cannot be dissolved in water and oil, so that cellulose in the water-in-oil emulsion is dispersed in liquid drops in a suspended state; in the cross-linking reaction process, cellulose does not participate in cross-linking and is embedded into the interior and the outer surface of a sodium alginate skeleton formed by the cross-linking reaction; after the original microspheres are treated with an etching solution, cellulose is degraded to different degrees, so that pore channels are reserved in the microspheres, the finally prepared sodium alginate microspheres are rich in pore channels, large in specific surface area and small in density, and the drug loading rate of the sodium alginate microspheres is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of drug carriers, and in particular to sodium alginate microspheres and a preparation method and application thereof. Background Art

[0002] Drug sustained-release microspheres are a type of functional polymer material that can embed and adsorb drugs on the surface or inside of polymers to make microsphere preparations for slow drug release. They have the advantages of extending absorption distribution and duration of action, reducing side effects caused by high and low blood drug concentrations, and reducing the amount and frequency of drug administration, thereby reducing toxic side effects. Among them, efficient drug loading and delivery carriers are very important.

[0003] Sodium alginate microspheres have become a new type of carrier with great development potential due to their excellent degradability, safety and harmlessness to the human body, and mild preparation process: Sodium alginate is a natural polysaccharide, a byproduct of extracting iodine and mannitol from kelp or sargassum of brown algae. It is mainly composed of two unit structures, β-D-mannuronic acid (M unit) and α-L-guluronic acid (G unit), and relies on β-1,4-glycosidic bonds to form different proportions of GM, MM and GG fragments to form copolymers; Sodium alginate can absorb water and swell to form hydrogels with a pore size of about 5 nm. Most drugs and proteins can be diffused and released from the gel, and DNA molecules and antibodies with larger particle sizes can be released through gel degradation. The gel skeleton formed by sodium alginate is pH-sensitive and is almost insoluble in an acidic environment, but swells in a weakly alkaline environment. After reaching the maximum swelling ratio, it begins to dissolve, which is conducive to the release of the encapsulated drugs inside it; However, the mechanical properties of sodium alginate deteriorate after forming a hydrogel, so it is generally used in the form of microspheres for drug delivery applications.

[0004] Currently, commonly used methods for preparing microspheres include emulsification, coagulation, precipitation polymerization, spray drying, grinding, etc. However, the prepared sodium alginate microspheres have small pores, high density, and small specific surface area, resulting in a relatively low drug loading rate. Summary of the invention

[0005] The invention provides a sodium alginate microsphere and a preparation method and application thereof, which solves the technical problem that the sodium alginate microsphere has small pores and a small specific surface area, resulting in a low drug loading rate.

[0006] The first aspect of the present invention provides a method for preparing sodium alginate microspheres, comprising:

[0007] adding a suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion;

[0008] Stirring and mixing the cross-linking agent and the water-in-oil emulsion to undergo a cross-linking reaction to obtain original microspheres;

[0009] The original microspheres are treated with an etching solution to obtain sodium alginate microspheres; the etching solution is used to promote cellulose degradation.

[0010] Optionally, the step of treating the original microspheres with an etching solution to obtain sodium alginate microspheres specifically includes:

[0011] Adding the original microspheres into an etching solution for reaction to obtain semi-finished microspheres;

[0012] The semi-finished microspheres are washed and dried to obtain sodium alginate microspheres.

[0013] Optionally, the stirring and mixing of the crosslinking agent and the water-in-oil emulsion to perform a crosslinking reaction to obtain the original microspheres specifically comprises:

[0014] Adding a crosslinking agent dropwise to the stirred water-in-oil emulsion, then homogenizing and completing the crosslinking reaction to obtain a mixture containing original microspheres;

[0015] A sufficient amount of oil phase detergent is added to the mixture and stirred, and the primary microspheres are separated from the mixture by centrifugation or natural sedimentation.

[0016] Optionally, before adding the suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion, the process comprises:

[0017] Adding sodium alginate into distilled water and stirring to obtain a sodium alginate solution;

[0018] Add cellulose to the sodium alginate solution and stir to obtain a suspension.

[0019] Optionally, before adding the suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion, the process comprises:

[0020] Adding sodium alginate and a porogen into distilled water, stirring to obtain a mixed solution;

[0021] Add cellulose to the mixed solution and stir to obtain a suspension.

[0022] Optionally, the cellulose is microfibrillated cellulose.

[0023] Optionally, the etching solution is a non-strong oxidizing acid.

[0024] Optionally, the homogenization process is performed using a homogenizer, and the homogenization pressure is 10 bar to 50 bar.

[0025] The second aspect of the present invention provides a sodium alginate microsphere prepared by any of the preparation methods described above.

[0026] The third aspect of the present invention provides sodium alginate microspheres prepared by any of the preparation methods described above or use of the sodium alginate microspheres in a drug delivery system.

[0027] It can be seen from the above technical solutions that the present invention has the following advantages:

[0028] The invention provides sodium alginate microspheres and a preparation method and application thereof. The preparation method comprises adding a suspension containing cellulose and sodium alginate to an oil phase for emulsification to form an oil-in-water emulsion, then stirring and mixing a crosslinking agent with the oil-in-water emulsion for crosslinking reaction to obtain original microspheres, and finally treating the original microspheres with an etching solution to obtain sodium alginate microspheres. In the present invention, since cellulose is insoluble in water and oil, cellulose in the water-in-oil emulsion is dispersed in a suspended state in the droplets; during the cross-linking reaction, cellulose does not participate in the cross-linking, but is embedded in the inner and outer surfaces of the sodium alginate microsphere skeleton formed by the cross-linking reaction; after the original microspheres are treated with an etching solution, the cellulose is degraded to varying degrees, thereby leaving pores of different pore sizes in the microspheres, and the finally prepared sodium alginate microspheres have abundant pores, a large specific surface area and a small density, thereby improving the drug loading rate of the sodium alginate microspheres; at the same time, the difference in pores inside and outside the prepared sodium alginate microspheres is also conducive to its adaptation to different drug loading requirements, and can achieve differentiated sustained release and simultaneous loading of drugs of different molecular weights, providing new possibilities for the loading of composite drugs, which is better than For example, the abundant pores in the outer layer allow the drug to be rapidly released from the microspheres to provide an initial high-dose release (burst effect), which is beneficial for immediate treatment. Over time, the drug can be released more slowly from the internal pores, thereby maintaining a stable drug concentration level and achieving continuous or sustained-release drug administration. In addition, since the etching solution is used to promote the degradation of cellulose, cellulose is widely distributed inside and on the surface of the sodium alginate microspheres and is in contact with the etching solution to varying degrees. Therefore, by controlling the reaction conditions and etching time, cellulose will have varying degrees of residue. The residual cellulose can enhance the mechanical strength of the prepared sodium alginate microspheres to a certain extent, avoid the collapse of the pore-rich sodium alginate microspheres, and facilitate drug loading. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0030] Figure 1 This is a microscope photo of sodium alginate microspheres prepared by the preparation method provided in Example 2 of the present invention;

[0031] Figure 2 This is a microscope photograph of sodium alginate microspheres prepared by the preparation method provided in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The embodiment of the present invention provides a sodium alginate microsphere and a preparation method and application thereof, which are used to solve the technical problem that the sodium alginate microsphere has a small pore size and a small specific surface area, resulting in a low drug loading rate.

[0033] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0035] Unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0036] The raw materials and reagents involved in the embodiments of the present invention are all commercially available.

[0037] Example 1

[0038] This embodiment is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0039] Step 11, weigh 10 parts of sodium alginate, add it into 90 parts of distilled water, place it in a magnetic stirrer for stirring, and form a sodium alginate solution.

[0040] It should be noted that, in the present invention, the mass fraction of the sodium alginate solution can be 5% to 15%; the stirring temperature is 55°C to 65°C, the stirring time is 15min to 30min, and the stirring process can be carried out by stirring equipment such as a magnetic stirrer and a mechanical stirrer.

[0041] Step 12: Add 1 part by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension.

[0042] Cellulose is a macromolecular polysaccharide insoluble in water or oil phase, and can be degraded into glucose or other smaller sugar molecules under acidic conditions. In this embodiment, microfibrillated cellulose is used, which has the characteristics of small size and high strength, and has good biocompatibility and biodegradability, and will not have adverse effects on the human body during the drug sustained release process. The diameter of the microfibrillated cellulose is 1nm to 100nm, and the length is less than 20μm. The stirring time in this step is 15min to 30min. The embedded amount of microfibrillated cellulose in the present invention is preferably 1% to 20% of the weight of sodium alginate.

[0043] Step 13, preparing the oil phase: adding surfactant Span 80 to the organic solvent liquid paraffin and stirring until uniform as the oil phase, the mass fraction of the surfactant is 2.5%.

[0044] In the present invention, the surfactant in the oil phase can be one of Span 40, Span 60, Span 80, Tween 20 or a mixture of two or more thereof; the organic solvent in the oil phase is one of liquid paraffin, cyclohexane, toluene or a mixture of two or more thereof; the amount of the surfactant added to the organic solvent can be 2.5% to 4.0%.

[0045] Step 14: adding the suspension to the oil phase, wherein the suspension has a volume ratio of 1:1 between the water phase and the oil phase, emulsifying at a certain rotation speed and dispersing evenly to form a water-in-oil (W / O type) emulsion.

[0046] It can be understood that in the water-in-oil emulsion system, water is dispersed in the oil in the form of small droplets, and the water droplets contain sodium alginate; while cellulose is mainly dispersed in the droplets and on the surface of the droplets; in the present invention, the volume ratio of the water phase to the oil phase is 1: (1~5), and the stirring speed during emulsification is 300rpm to 500rpm.

[0047] Step 15: Add 0.6 g / ml CaCl dropwise 2 One part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then cross-linked and cured for 2 hours under stirring at a speed of 300 to 500 rpm to obtain a mixture containing original microspheres.

[0048] The crosslinking agent can be a divalent metal ion solution, with Ca 2+ As a representative example, CaCl 2 The solution concentration is preferably 0.5 g / ml to 0.8 g / ml, CaCl 2 The higher the concentration of the solution, the better, to ensure complete gelation and to prevent the undissolved CaCl 2 Can be washed out in subsequent steps; CaCl 2 The amount of solution added is 10% of the mass of sodium alginate; in the present invention, CaCl 2 The stirring speed of the water-in-oil emulsion in the case of aqueous solution is 30 rpm to 100 rpm.

[0049] During the cross-linking reaction, the cross-linking agent will react with the carboxyl groups on the sodium alginate molecular chain to form a solid sodium alginate skeleton with a three-dimensional network structure, which is the core of the original microspheres. Cellulose does not participate in the cross-linking reaction, but is embedded in the interior and exterior surface of the newly formed sodium alginate microsphere skeleton.

[0050] Step 16: Add sufficient amount of petroleum ether to the mixture, stir, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0051] The oil phase detergent is used to remove the oil phase components and by-products in the mixture that are not easily soluble in water. It must have a good ability to dissolve or emulsify oil. Organic solvents that will not affect sodium alginate and cellulose, such as petroleum distillate solvents, can be selected; petroleum ether is used as the oil phase detergent in this step.

[0052] Step 17, adding the separated original microspheres into hydrochloric acid with a hydrogen ion concentration of 4 mol / L, the mass of the hydrochloric acid being 5% of the original microspheres, and reacting for 40 minutes to obtain semi-finished microspheres.

[0053] In the present invention, the etching solution is used to promote the degradation of cellulose; sodium alginate is pH-sensitive and is almost insoluble in an acidic environment. It will swell and degrade in an alkaline environment, while cellulose is easily degraded into glucose or other smaller sugar molecules under acidic conditions, so that a pore structure is formed at the original location of the cellulose. Therefore, non-strong oxidizing acid solutions such as citric acid, acetic acid, and hydrochloric acid can be used as etching solutions, but strong oxidizing acid solutions cannot be used as etching solutions, which will carbonize the sodium alginate; the hydrogen ion concentration of the non-strong oxidizing acid solution is preferably 3 mol / L to 6 mol / L, the added amount is 1% to 8% of the original microsphere mass, and the etching reaction time is 30 minutes to 1 hour.

[0054] It can be understood that when the original microspheres are etched with an etching solution, the cellulose inside and outside the original microspheres partially degrades after reacting with the etching solution, leaving composite pores with different pore sizes between the outer layer and the inner layer, thereby enriching the pore structure of the microspheres, increasing the specific surface area of ​​the final sodium alginate microspheres, reducing the density of the sodium alginate microspheres, and increasing the drug loading rate of the sodium alginate microspheres;

[0055] The difference in pores inside and outside the prepared sodium alginate microspheres is also conducive to their adaptation to different drug loading requirements, and can achieve differentiated sustained release and simultaneous loading of drugs of different molecular weights, providing new possibilities for the loading of complex drugs. For example, the rich pores in the outer layer allow the drug to be quickly released from the microspheres to provide an initial high-dose release (burst effect), which is conducive to immediate treatment; and over time, the drug can be released more slowly from the internal pores, thereby maintaining a stable drug concentration level and achieving continuous or sustained-release drug administration.

[0056] In addition, since the etching solution is used to promote the degradation of cellulose, cellulose is widely distributed inside and on the surface of the sodium alginate microspheres and is in contact with the etching solution to varying degrees. Therefore, by controlling the reaction conditions and etching time, cellulose will remain to varying degrees. The residual cellulose can enhance the mechanical strength of the prepared sodium alginate microspheres to a certain extent, avoid the collapse of pore-rich sodium alginate microspheres, and facilitate drug loading.

[0057] Step 18: Wash the semi-finished microspheres repeatedly with acetone, ethanol and water for three times, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres.

[0058] Acetone and ethanol can dissolve some polar residues that cannot be effectively removed by oil-phase detergents, and can also help further clean organic matter that may remain on the microspheres, ensuring that no harmful organic solvents remain in the final product; specifically, in the present invention, washing with acetone, ethanol and water is required in sequence, and repeated three or more times, the drying temperature is 40°C to 50°C, and the drying time is 4 hours to 6 hours.

[0059] Example 2

[0060] This embodiment is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0061] Step 21, weigh 10 parts of sodium alginate, add it into 90 parts of distilled water, place it in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0062] Step 22: Add 1 part by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension; the stirring time is 15 to 30 minutes.

[0063] Step 23: Add surfactant Span 80 into the organic solvent liquid paraffin and stir until uniform as the oil phase, and the mass fraction of the surfactant is 2.5%.

[0064] Step 24: adding the suspension to the oil phase, wherein the suspension has a volume ratio of 1:1 between the water phase and the oil phase, emulsifying at a certain rotation speed and dispersing evenly to form a water-in-oil (W / O type) emulsion.

[0065] Step 25: Add 0.6 g / ml CaCl dropwise 2 1 part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then homogenized by a homogenizer, and the cross-linking and curing reaction is completed at a homogenization pressure of 30 Bar to obtain a mixture containing original microspheres.

[0066] It should be noted that the homogenizing effect of the homogenizer can improve the uniformity of the microsphere particle size and reduce the particle size span; and according to the cell's uptake of microsphere particles of different sizes and through the pressure control of the homogenizer, sodium alginate microspheres with uniform particle sizes ranging from 10μm to 200μm can be selectively prepared to meet the needs of sustained-release drug microspheres in different scenarios, control the sustained-release effect, and can be used for different purposes such as injection, oral administration, nasal drops, subcutaneous implantation or targeted preparations.

[0067] Step 26: Add sufficient amount of petroleum ether to the mixture, stir, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0068] Step 27, adding the separated original microspheres into 4 mol / L hydrochloric acid, the mass of which is 5% of the original microspheres, and reacting for 40 minutes to obtain semi-finished microspheres.

[0069] Step 28, wash the semi-finished microspheres repeatedly with acetone, ethanol and water for 3 times respectively, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0070] The morphology of the sodium alginate microspheres prepared by the preparation method provided in Example 2 can be found in Figure 1 , cellulose can be seen embedded in the microspheres.

[0071] Example 3

[0072] This embodiment is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0073] Step 31, weigh 5 parts of sodium alginate, add it into 95 parts of distilled water, place it in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0074] Step 32: Add 0.75 parts by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension; the stirring time is 15 to 30 minutes.

[0075] Step 33: Add surfactants Span 80 and Tween 20 into the organic solvent cyclohexane and stir until uniform as the oil phase, and the mass fraction of the surfactant is 3%.

[0076] Step 34: Add the suspension to the oil phase, the suspension being a water phase with a volume ratio of 1:3 to the oil phase, emulsify at a certain speed, and disperse evenly to form a water-in-oil (W / O) emulsion.

[0077] Step 35: Add 0.5 g / ml CaCl dropwise 2 0.5 parts of the aqueous solution was added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition was completed within 10 minutes. Then, it was homogenized by a homogenizer, and the cross-linking and curing reaction was completed at a homogenization pressure of 50 Bar to obtain a mixture containing original microspheres.

[0078] Step 36: Add sufficient amount of petroleum ether to the mixture, stir it, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0079] Step 37, adding the separated original microspheres into 3 mol / L hydrochloric acid, the mass of which is 8% of the original microspheres, and reacting for 1 hour to obtain semi-finished microspheres.

[0080] Step 38, wash the semi-finished microspheres repeatedly with acetone, ethanol and water for 3 times respectively, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0081] Example 4

[0082] This embodiment is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0083] Step 41, weigh 15 parts of sodium alginate, add it into 85 parts of distilled water, place it in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0084] Step 42: Add 3 parts by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension; the stirring time is 15 to 30 minutes.

[0085] Step 43: Add surfactant Span 40 into the organic solvent toluene and stir until uniform as the oil phase, and the mass fraction of the surfactant is 4%.

[0086] Step 44, add the suspension to the oil phase, the suspension is used as the water phase and the oil phase has a volume ratio of 1:5, emulsifies at a certain speed, and disperses evenly to form a water-in-oil (W / O type) emulsion.

[0087] Step 45: Add 0.8 g / ml CaCl dropwise 2 0.15 parts of the aqueous solution was added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition was completed within 10 minutes. Then, it was homogenized by a homogenizer, and the cross-linking and curing reaction was completed at a homogenization pressure of 10 Bar to obtain a mixture containing original microspheres.

[0088] Step 46: Add sufficient amount of petroleum ether to the mixture, stir it, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0089] Step 47, adding the separated original microspheres into 6 mol / L hydrochloric acid, the mass of which is 1% of the original microspheres, and reacting for 30 minutes to obtain semi-finished microspheres.

[0090] Step 48, wash the semi-finished microspheres repeatedly with acetone, ethanol and water for 3 times respectively, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0091] Example 5

[0092] This embodiment is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0093] Step 51, weigh 10 parts of sodium alginate and 0.07 parts of porogen polyethylene glycol, add them to 90 parts of distilled water, place in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0094] In the present invention, the addition of porogen can bring more pores to the microsphere as a whole. Compared with cellulose, the distribution of porogen in the water phase is more uniform. The porogen can be one or a mixture of two or more of polyethylene glycol, polyvinyl pyrrolidone and urea. The amount of porogen added is 0.5% to 1% of the mass of sodium alginate.

[0095] Step 52: Add 1 part by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension; the stirring time is 15 to 30 minutes.

[0096] Step 53: Add surfactant Span 80 into the organic solvent liquid paraffin and stir until uniform as the oil phase, and the mass fraction of the surfactant is 2.5%.

[0097] Step 54: Add the suspension to the oil phase, wherein the suspension has a volume ratio of 1:1 between the water phase and the oil phase, and emulsify at a certain speed to disperse evenly to form a water-in-oil (W / O) emulsion.

[0098] Step 55: Add 0.6 g / ml CaCl dropwise 2 1 part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then homogenized by a homogenizer, and the cross-linking and curing reaction is completed at a homogenization pressure of 30 Bar to obtain a mixture containing original microspheres.

[0099] Step 56: Add sufficient amount of petroleum ether to the mixture, stir it, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0100] Step 57, adding the separated original microspheres into 4 mol / L hydrochloric acid, the mass of which is 5% of the original microspheres, and reacting for 40 minutes to obtain semi-finished microspheres.

[0101] Step 58, wash the semi-finished microspheres repeatedly with acetone, ethanol and water for three times respectively, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0102] Example 6

[0103] This embodiment provides an application of sodium alginate microspheres prepared by the preparation method provided in any of the above embodiments in a drug delivery system, which can play a role in simultaneous loading and differentiated sustained release of drugs of different molecular weights in the drug delivery system.

[0104] Comparative Example 1

[0105] This comparative example is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0106] Step 61, weigh 10 parts of sodium alginate, add it into 90 parts of distilled water, place it in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0107] Step 62: Add 1 part by weight of microfibrillated cellulose to the sodium alginate solution and stir to form a suspension; the stirring time is 15 to 30 minutes.

[0108] Step 63: Add surfactant Span 80 into the organic solvent liquid paraffin and stir until uniform as the oil phase, and the mass fraction of the surfactant is 2.5%.

[0109] Step 64, adding the suspension to the oil phase, wherein the suspension has a volume ratio of 1:1 between the water phase and the oil phase, emulsifying at a certain rotation speed, and dispersing evenly to form a water-in-oil (W / O type) emulsion.

[0110] Step 65: Add 0.6 g / ml CaCl dropwise 2 1 part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then homogenized by a homogenizer, and the cross-linking and curing reaction is completed at a homogenization pressure of 30 Bar to obtain a mixture containing original microspheres.

[0111] Step 66: Add sufficient amount of petroleum ether to the mixture, stir it, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0112] Step 67, wash the original microspheres repeatedly with acetone, ethanol and water for three times, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0113] Comparative Example 2

[0114] This comparative example is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0115] Step 71, weigh 10 parts of sodium alginate and 0.07 parts of porogen polyethylene glycol, add them to 90 parts of distilled water, place in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0116] Step 72: Add surfactant Span 80 into the organic solvent liquid paraffin and stir until uniform as the oil phase. The mass fraction of the surfactant is 2.5%.

[0117] Step 73, add the suspension to the oil phase, the suspension having a volume ratio of 1:1 between the water phase and the oil phase, emulsify at a certain rotation speed, and disperse evenly to form a water-in-oil (W / O type) emulsion.

[0118] Step 74: Add 0.6 g / ml CaCl dropwise 21 part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then homogenized by a homogenizer, and the cross-linking and curing reaction is completed at a homogenization pressure of 30 Bar to obtain a mixture containing original microspheres.

[0119] Step 75: Add sufficient amount of petroleum ether to the mixture, stir, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0120] Step 76: Wash the original microspheres repeatedly with acetone, ethanol and water for three times, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0121] Comparative Example 3

[0122] This comparative example is a preparation of sodium alginate microspheres, and the preparation method specifically includes:

[0123] Step 81, weigh 10 parts of sodium alginate and 0.07 parts of porogen polyethylene glycol, add them to 90 parts of distilled water, place in a magnetic stirrer for stirring, and form a sodium alginate solution; the stirring temperature is 55° C. to 65° C., and the stirring time is 15 min to 30 min.

[0124] Step 82: Add surfactant Span 80 into the organic solvent liquid paraffin and stir until uniform as the oil phase. The mass fraction of the surfactant is 2.5%.

[0125] Step 83, adding the suspension to the oil phase, wherein the suspension has a volume ratio of 1:1 between the water phase and the oil phase, emulsifying at a certain rotation speed, and dispersing evenly to form a water-in-oil (W / O type) emulsion.

[0126] Step 84: Add 0.6 g / ml CaCl dropwise 2 1 part of the aqueous solution is added to the oil-in-water emulsion in a stirring state at a stirring speed of 50 rpm, and the addition is completed within 10 minutes, and then homogenized by a homogenizer, and the cross-linking and curing reaction is completed at a homogenization pressure of 30 Bar to obtain a mixture containing original microspheres.

[0127] Step 85: Add sufficient amount of petroleum ether to the mixture, stir, and separate the original microspheres from the mixture by centrifugation or natural sedimentation.

[0128] Step 86: Add the separated original microspheres into 4 mol / L hydrochloric acid, the mass of which is 5% of the original microspheres, and react for 40 minutes to obtain semi-finished microspheres.

[0129] Step 87, wash the semi-finished microspheres repeatedly with acetone, ethanol and water for three times respectively, dry them, remove the solvent inside the microspheres, and obtain sodium alginate microspheres; the drying temperature is 40° C. to 50° C., and the drying time is 4 hours to 6 hours.

[0130] The morphology of the sodium alginate microspheres prepared by the preparation method provided in Comparative Example 3 can be found in Figure 2 .

[0131] Experimental Example 1

[0132] Eight portions of sodium alginate microspheres were prepared using the preparation methods of Examples 1 to 5 and Comparative Examples 1 to 3, and the density and particle size tests were performed respectively:

[0133] Density test process: Take 1 g of sodium alginate microspheres, disperse them in 1 mL of purified water and add them into a 5 mL measuring cylinder. Let it stand at room temperature for 24 h. Take photos at 0 h, 8 h, 12 h, and 24 h, respectively, and record the position and moving distance of the interface between water and sodium alginate microspheres. The corresponding moving distance divided by the measurement time is the sedimentation or floating rate v of the sodium alginate microspheres. The density of the microspheres can be estimated according to the Stokes sedimentation formula:

[0134]

[0135] Where: v is the final particle settling velocity, cm / s; h is the settling distance, cm; t is the settling time, s; ρ i is the density of the solid, g / cm³; d is the average particle size of spherical solid particles, cm.

[0136] Particle size test process: Take 1 g of microspheres, disperse them in 1 mL of purified water, and inject them into a laser particle size analyzer to measure the average particle size and D 90 (Indicates the particle size corresponding to the cumulative volume distribution reaching 90%. This means that 90% of the particle volume is less than or equal to this size), D 50 (indicates the particle size corresponding to when the cumulative volume distribution reaches 50%, also called median particle size or average particle size) and D 10 (indicates the particle size corresponding to when the cumulative volume distribution reaches 10%); D 90 , D 50 and D 10 The span value (Span) of the microsphere sample can be calculated, which indicates the consistency of the particle size of the microsphere sample. The closer the Span value is to 0, the more uniform the particle size and the higher the size uniformity.

[0137]

[0138] The density and particle size test results of eight sodium alginate microspheres can be found in the following table:

[0139]

[0140] Table 1 Density and particle size test results of sodium alginate microspheres

[0141] Analysis of the above sodium alginate density and particle size test results shows that:

[0142] 1) Microfibrillated cellulose is added to the sodium alginate microspheres prepared by the preparation method provided in Examples 1 to 4, and the cellulose in the microspheres is etched by hydrochloric acid to leave composite pores with different outer and inner pore sizes, so that the density is significantly lower than that of sodium alginate; however, since the sodium alginate microspheres prepared in Example 1 are not treated by a homogenizer, the particle size span is large, which is not conducive to the precise use of loaded drugs in the same scenario; while the particle size span of the sodium alginate microspheres treated by a homogenizer in Examples 2 to 4 is close to 0, and the size of the microspheres is relatively uniform.

[0143] 2) In Example 5, a porogen is additionally added, so that its pore structure is richer than that of Example 2 and the density of microspheres is smaller.

[0144] 3) In Comparative Example 1, although microfibrillated cellulose was added and homogenized by a homogenizer, hydrochloric acid etching was not used, and its density was close to that of sodium alginate.

[0145] 4) In Comparative Example 2, hollow channels were obtained by simply using a porogen and the mixture was homogenized using a homogenizer. In Comparative Example 3, pores were prepared using a porogen and the mixture was homogenized using a homogenizer, but microfibrillated cellulose was not added. The density of the sodium alginate microspheres prepared in Comparative Examples 2 and 3 was higher than that of the sodium alginate microspheres prepared in Example 2 by adding microfibrillated cellulose and etching with hydrochloric acid.

[0146] Experimental Example 2

[0147] Eight portions of sodium alginate microspheres were prepared by the preparation methods of Examples 1 to 5 and Comparative Examples 1 to 3, and tanshinone IIA was used as a model drug to test the drug loading rates of the eight portions of sodium alginate microspheres, respectively. The test process is as follows;

[0148] Draw a standard curve of Tanshinone IIA solution with different concentrations;

[0149] A certain concentration of Tanshinone IIA solution was prepared, and sodium alginate microspheres were added to the Tanshinone IIA solution under stirring conditions, stirred at a high speed of 400-500 r / min for 10-15 minutes, centrifuged at a speed of 5000-6000 r / min for 3-5 minutes, washed with anhydrous ethanol and distilled water in turn, and dried to obtain drug-loaded sodium alginate microspheres;

[0150] Weigh an appropriate amount of drug-loaded microspheres as M 1, added to trisodium citrate (5 mL, 0.06 mol / L) and sodium bicarbonate (5 mL, 0.2 mol / L), when the pH value ranged from 5.0 to 7.6, trisodium citrate and SA were electrostatically attracted, causing the microspheres to dissociate and release tanshinone IIA;

[0151] The absorbance of the released drug was measured by ultraviolet spectrophotometry at 270 nm to obtain its concentration, and the mass of the microsphere-loaded tanshinone IIA was obtained as M 2 ;

[0152] Calculate the drug loading rate, drug loading rate = M 2 / M 1 *100%.

[0153] The test results of Tanshinone IIA drug loading rate of eight sodium alginate microspheres can be found in the table below:

[0154]

[0155] Table 2 Test results of tanshinone IIA loading rate of sodium alginate microspheres

[0156] Analysis of the test results of the tanshinone IIA loading rate of the above-mentioned sodium alginate microspheres revealed that:

[0157] 1) Although the drug loading rate of the sodium alginate microspheres prepared in Example 1 is not bad, due to the wide particle size distribution, it is not conducive to the application in the same scenario, and the drug loading rate is not as good as that of the sodium alginate microspheres homogenized by a homogenizer in Examples 2 to 4;

[0158] 2) The drug loading rates of the sodium alginate microspheres prepared in Examples 2 to 4 are all relatively high. The hydrochloric acid etching of the microfibrillated cellulose causes the sodium alginate microspheres to form composite pores with different pore sizes in the outer layer and the inner layer, enriching the pores of the sodium alginate microspheres, with more cavity structures, and increasing the specific surface area. After homogenization treatment, the particle size is more uniform, and the drug loading rate is significantly improved.

[0159] 3) The addition of porogen in Example 5 further enriched the hollow pore structure inside the sodium alginate microspheres, thereby further improving the drug loading rate.

[0160] 4) The sodium alginate microspheres prepared in Comparative Example 1 have fewer pores and a very low drug loading rate.

[0161] 5) In comparative example 2, only pore-forming agent was used, the pore structure was relatively simple, and the drug loading rate did not reach the ideal value.

[0162] 6) In Comparative Example 3, pores were prepared using a porogen without adding microfibrillated cellulose. The pore structure of the prepared sodium alginate microspheres had low mechanical strength and was easily collapsed, affecting drug loading, resulting in a lower drug loading rate than the sodium alginate microspheres prepared in Example 5.

[0163] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing sodium alginate microspheres, characterized in that: include: adding a suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion; Stirring and mixing the cross-linking agent and the water-in-oil emulsion to undergo a cross-linking reaction to obtain original microspheres; The original microspheres are treated with an etching solution to obtain sodium alginate microspheres; the etching solution is used to promote cellulose degradation.

2. The preparation method according to claim 1, characterized in that: The method of treating the original microspheres with an etching solution to obtain sodium alginate microspheres specifically includes: Adding the original microspheres into an etching solution for reaction to obtain semi-finished microspheres; The semi-finished microspheres are washed and dried to obtain sodium alginate microspheres.

3. The preparation method according to claim 1, characterized in that: The stirring and mixing of the crosslinking agent and the water-in-oil emulsion to perform a crosslinking reaction to obtain the original microspheres specifically comprises: Adding a crosslinking agent dropwise to the stirred water-in-oil emulsion, then homogenizing and completing the crosslinking reaction to obtain a mixture containing original microspheres; A sufficient amount of oil phase detergent is added to the mixture and stirred, and the primary microspheres are separated from the mixture by centrifugation or natural sedimentation.

4. The preparation method according to claim 1, characterized in that: The method of adding the suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion comprises: Adding sodium alginate into distilled water and stirring to obtain a sodium alginate solution; Add cellulose to the sodium alginate solution and stir to obtain a suspension.

5. The preparation method according to claim 1, characterized in that: The method of adding the suspension containing cellulose and sodium alginate to the oil phase for emulsification to form a water-in-oil emulsion comprises: Adding sodium alginate and a porogen into distilled water, stirring to obtain a mixed solution; Add cellulose to the mixed solution and stir to obtain a suspension.

6. The preparation method according to claim 4 or 5, characterized in that: The cellulose is microfibrillated cellulose.

7. The preparation method according to claim 1, characterized in that: The etching solution is a non-strong oxidizing acid.

8. The preparation method according to claim 3, characterized in that: The homogenization process is carried out using a homogenizer, and the homogenization pressure is 10 bar to 50 bar.

9. A sodium alginate microsphere, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the sodium alginate microspheres prepared by the preparation method according to any one of claims 1 to 8 or the sodium alginate microspheres according to claim 9 in a drug delivery system.